Medos da compaixão e engajamento nas medidas de distanciamento social no enfrentamento à COVID-19 - Pfeiffer, Sandiléia (2021)
Compassion and its benefits for individuals have been focus of investigation in Psychology nowadays. It is evidenced that compassion may promote mental and physical health and the development of a compassionate posture tends to contribute to the involvement in collective actions in a collaborative and prosocial way. However, individuals with a history of neglect, abuse and exposure to shame may have difficulties of being compassionate due to their fears of compassion. Since December 2019, the entire world has been facing challenges imposed by the new coronavirus pandemic. Emotional, physical, social and economic impacts have been faced in response to the virus, which demanded social distance measures in order to contain its spread. Demanding individual efforts to protect the community, social distancing protocols are a challenge for governments around the world, who are facing great difficulties to keep the population engaged. In order to understand the role of fears of compassion in coping with this pandemic, this study aimed to investigate underlying motivations and perceptions that influence the individuals’ decision to follow or not the social distance measures. It was also investigated these perceptions’ association with difficulties in emotion regulation and fears of compassion, and a model that tested the role of fears of compassion in the impact of following the protocols against COVID-19 was proposed. In this sense, two studies were conducted: the first one held a cross-cultural adaptation process and to investigate evidence of validity from the Fears of Compassion Scales for use in Brazil. After cross-cultural adaptation and content validation process, 284 adults (mean age = 36.47) answered a sociodemographic questionnaire and the Fears of Compassion Scales adapted to the Brazilian Portuguese. Exploratory Factor Analysis, Cronbach's alpha and McDonald's omega tests indicated satisfactory internal consistency and unifatorial solution for each of the three scales. In addition, network analysis was conducted to verify how scale items were distributed in the investigated sample, highlighting items with greater influence of activation. Results indicate that the instrument is adequate to be used in Brazil. The second study aimed to investigate the associations between fears of compassion, difficulties in emotion regulation, compliance with social distance measures and reasons that influence decision making about following the health protocols related to COVID-19 pandemic. 284 adults (mean age = 36.47), through online data collection, answered questions about coping with the pandemic, the Brazilian version of Fears of Compassion Scales and the Difficulties in Emotion Regulation Scale. The results indicated that external reasons, such as economic obligations or other people's judgment, have no effect on social distance measures compliance. However, emotional exhaustion caused a 28% decrease in adopting health protocols related to COVID-19 pandemic. On the other hand, reasons related to prosocial motivation had shown to increase in 34% the engagement with these referred measures. A model tested through path analysis explained 32% of the variance of following the health protocols related to COVID-19 pandemic, indicating that fears of compassion impact on attending to social distance measures in two ways. Fear of expressing compassion for others decreases the engagement in health protocols related to COVID-19 pandemic impacting in prosocial motivation. Fears of expressing compassion for oneself and others increased the difficulties in emotion regulation in response to the pandemic, decreasing level of compliance with these referred measures by reasons of emotional exhaustion. The results of the study contributed to understand underlying factors related to adherence to the measures and behaviors to contain the new coronavirus. Also, these results promote a discussion about social values that tend to buster competitiveness and may difficult the development of collaborative mentalities. This discussion is not only important in the COVID-19 pandemic scenario, but in other social actions that require collective efforts, such as climate change and social, racial and gender inequalities.